Correction of Class II division 2 with crowding and bilateral fully transposed impacted mandibular canines - Han Lei; Mei Li; Zhang Caixia; Wu Tuojiang; Wang Congyue; Li Huang (Sciendo, 2022)
Maxillary canine impaction has been extensively reported, but studies of mandibular canine impaction are relatively few. Clinical studies and reports of experience treating mandibular canine impaction are of clinical benefit to both orthodontists and dentists.